Airway Considerations in Pediatric Neurosurgical Patients - Bhagat, Hemant; Bloria, Summit Dev; Kapil, Sonia; Kaloria, Narender (Indian Journal of Neurosurgery, 2020)
Managing airway in pediatric neurosurgical patients can prove to be challenging. In this article, we wish to touch upon the specific airway considerations to be kept in mind while caring for these patients during neurosurgeries.
Keywords: pediatric patients’ airway